Determination of Metals Present in Textile Dyes Using Laser-Induced Breakdown Spectroscopy and Cross-Validation Using Inductively Coupled Plasma/Atomic Emission Spectroscopy. (28th August 2017) - Rehan, K.; Rehan, I.; Sultana, S.; Khan, M. Zubair; Farooq, Z.; Mateen, A.; Humayun, M.
Abstract : Laser-induced breakdown spectroscopy (LIBS) was used for the quantitative analysis of elements present in textile dyes at ambient pressure via the fundamental mode (1064 nm) of a Nd:YAG pulsed laser. Three samples were collected for this purpose. Spectra of textile dyes were acquired using an HR spectrometer (LIBS2000+, Ocean Optics, Inc.) having an optical resolution of 0.06 nm in the spectral range of 200 to 720 nm. Toxic metals like Cr, Cu, Fe, Ni, and Zn along with other elements like Al, Mg, Ca, and Na were revealed to exist in the samples. The %-age concentrations of the detected elements were measured by means of standard calibration curve method, intensities of every emission from every species, and calibration-free (CF) LIBS approach. Only Sample 3 was found to contain heavy metals like Cr, Cu, and Ni above the prescribed limit. The results using LIBS were found to be in good agreement when compared to outcomes of inductively coupled plasma/atomic emission spectroscopy (ICP/AES).